Financial frictions in the euro area: a Bayesian assessment - Stefania Villa (European Central Bank (ECB), 2013)
This paper compares from a Bayesian perspective three dynamic stochastic general equilibrium models in order to analyse whether financial frictions are empirically relevant in the Euro Area (EA) and, if so, which type of financial frictions is preferred by the data. The models are: (i) Smets and Wouters (2007) (SW); (ii) a SW model with financial frictions originating in non-financial firms à la Bernanke et al. (1999), (SWBGG); and (iii) a SW model with financial frictions originating in financial intermediaries, à la Gertler and Karadi (2011), (SWGK). The comparison between the three estimated models is made along different dimensions: (i) the Bayes factor; (ii) business cycle moments; and (iii) impulse response functions. The analysis of the Bayes factor and of simulated moments provides evidence in favour of the SWGK model. This paper also finds that the SWGK model outperforms the SWBGG model in forecasting EA inflationary pressures in a Phillips curve specification.
Keywords: C11; E44; 330; Bayesian estimation; DSGE Models; Financial Frictions